Заздрісність у контексті девіантної поведінки військовослужбовців - Мілорадова, Н. Е.; Miloradovа, N. E.; Філоненко, В. М.; Filonenko, V. M.; Natalia Miloradova; Володимир Філоненко (Габітус. - 2023. - Вип. 51. - С. 217-221, 2023)
У роботі проаналізовано особливості виникнення і переживання заздрості чоловіками та жінками військовослужбовцями в контексті правової поведінки. У проведеному дослідженні був використаний комплекс взаємодоповнюючих методів: аналіз наукової літератури щодо проблеми дослідження, бесіда, анкетування, тестування. Також закцентовано увагу на заздрості як потужній емоції, що включає в себе негативні почуття невдоволення, спрямовані до вищого зовнішнього джерела. Заздрісні люди бажають отримати привабливі якості, досягнення або власність іншої людини. У висновках авторами зазначається, що заздрість реалізується на особистісному та соціальному рівнях, зумовлює формування самовідношення та самооцінювання, прояв схильності до різних видів девіацій, визначає особливості та результати адаптації особистості у змінному світі. Етикопсихологічні феномени соціальної поведінки багато в чому залежать від гендерної приналежності суб'єкта.

The feeling of irritation caused by some advantage, superiority, well-being of another is often hidden by a person from others, and sometimes from himself. Why does a feeling of envy arise, how and why? This question is very important both for understanding the psychology of an individual's behavior and for explaining a number of events in society that have developed historically and are happening today. The concept of envy can be interpreted as a state or feeling, experiencing hostility towards another person, in relation to his happiness, well-being, success, morality, cultural level or material advantage. Envy is a kind of recognition of the superiority, success, well-being of another, combined with a feeling of annoyance, hostility towards the achiever. Envy exhibits a demanding desire to have, to possess at the level of another or even to surpass him, to dominate. The article analyzes the peculiarities of the occurrence and experience of envy by male and female military personnel in the context of legal behavior. A set of complementary methods was used in the conducted research: analysis of scientific literature on the research problem, interview, questionnaire, testing. Also, attention is focused on envy as a powerful emotion, which includes negative feelings of dissatisfaction directed to a higher external source. Envious people want to get attractive qualities, achievements or possessions of another person. In the conclusions of the authors, it is noted that envy is realized at the personal and social levels, determines the formation of self-attitude and self-evaluation, the manifestation of a tendency to various types of deviations, determines the peculiarities and results of personal adaptation in a changing world. Ethical and psychological phenomena of social behavior largely depend on the gender of the subject. In the results of the study, certain possible directions of future research of the considered problem are indicated: the study of individual and psychological determinants of envy; determination of relationships between the parameters of envy and such characteristics of the subject as intelligence, volitional qualities of the individual, dynamic properties of individuality.

В работе проанализированы особенности возникновения и переживания зависти мужчинами и женщинами военнослужащими в контексте правового поведения. Акцентировано внимание на зависти как мощной эмоции, включающей в себя отрицательное чувство недовольства, направленное на высший внешний источник. Завистливые люди желают получить привлекательные качества, достижение или собственность другого человека. В выводах авторами отмечается, что зависть реализуется на личном и социальном уровнях, предопределяет формирование самоотношения и самооценку, проявление склонности к разным видам девиаций, определяет особенности и результаты адаптации личности в изменяющемся мире. Этикопсихологические феномены социального поведения во многом зависят от гендерной принадлежности субъекта.
Envy in the context of deviant behavior of military personnel
Keywords: заздрість; девіантна поведінка; асоціальна поведінка; військовослужбовці; envy; deviant behavior; antisocial behavior; military personnel